2015
DOI: 10.1016/j.otsr.2015.02.011
|View full text |Cite
|
Sign up to set email alerts
|

The effect of laminae lesion on thoraco-lumbar fracture reduction

Abstract: In upper lumbar burst fractures, complete lamina fracture is an indicator of injury severity. When detected preoperatively on CT or MRI scanning, it should be operated by open book laminectomy even if the patient is neurologically intact since it carries a high risk of neural entrapment, and its presence affects the intraoperative postural and instrumental trials for anterior vertebral height restoration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0
7

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 27 publications
0
16
0
7
Order By: Relevance
“…Several studies have documented herniation of the neural elements between the fractured lamina edges, which can cause further neurological compromise [ 17 18 ]. Skiak et al [ 8 ] showed a strong association between the occurrence of a complete lamina fracture and a dural tear. In tears of dura, the likelihood of neural entrapment have been demonstrated at 33% in complete lamina fractures and 15% in incomplete lamina fractures.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Several studies have documented herniation of the neural elements between the fractured lamina edges, which can cause further neurological compromise [ 17 18 ]. Skiak et al [ 8 ] showed a strong association between the occurrence of a complete lamina fracture and a dural tear. In tears of dura, the likelihood of neural entrapment have been demonstrated at 33% in complete lamina fractures and 15% in incomplete lamina fractures.…”
Section: Discussionmentioning
confidence: 99%
“…In tears of dura, the likelihood of neural entrapment have been demonstrated at 33% in complete lamina fractures and 15% in incomplete lamina fractures. Surgeons are advised to be particularly careful with patients with complete lamina fractures [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations